TECHNOLOGIES INTEGRATED TO THE CLASSROOM - Valdemir da Silva, Antonio (Revista Gênero e Interdisciplinaridade, 2023)
This article presents a theoretical context on technologies integrated into the classroom, linked to quality in schools. The purpose of this is to show the importance of the process of using technologies integrated into classrooms as an advantage to achieve the quality of learning within the school. Faced with the demanding educational world and a globalized society, technological tools in classrooms must be designed with quality. The future of an educational institution depends on the technologies integrated into the classroom and can be able to satisfy the requirements of educational quality. These integrated technologies can provide students, today, more than ever, with a passport to the student’s digital development, where it is a topic to think about and reflect on the growth of learning acquired at school, where all this belongs to the use of effective educational tools. So-called digital teachers and students are the only ones capable of self-direction and development, as they are the people who make things happen, who drive learning, produce progress and provide services in an exceptional way. And to maintain good quality learning as a differential, the school must seek to keep its staff always well-prepared and technologically advanced.